The taxonomic status of Copemyodon ecuadorensis (Rodentia, Cricetidae), a supposedly extinct muroid from the Ecuadorean Quaternary - Moreno, Pablo (2017)
Copemyodon ecuadorensis was described as a non-sigmodontine extinct cricetid from two rich fossiliferous localities in northern Ecuador. It was hypothesized as being related to both the fossil genus Copemys and the living Peromyscus and, as such, is an example of an independent "copemyine-neotomine" attempt to colonize South America. Here, we re-study the holotype of C. ecuadorensis concluding that it cannot be separated from Reithrodontomys (Cricetidae, Neotominae) at a generic level. Copemyodon constitutes a junior synonym of Reithrodontomys. There are recent populations of Reithrodontomys in Ecuador and most likely it comprises several species. In this context, seems convenient to retain ecuadorensis as a species of Reithrodontomys until an appropriate revision of this genus is performed, although we identify morphological similarities between Reithrodontomys ecuadorensis and the nominal form Reithrodontomys soederstroemi.